Comparison Of Giving The Rebozo Technique And Oxytocin Massage To The Length Of Labor At The Sukatani Health Center, Bekasi Regency, West Java - Siti Yayu Ratnasari; Feva Tridiyawati (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Complications in the length of time of delivery can cause the mother's blood flow through the placenta to decrease so that it has an impact on the occurrence of asfexia in newborns. One way to accelerate the progress of labor is by giving the rebozo technique and oxytocin massage. The results of the data report from the Dian Medika Jayanti Clinic, Tangerang Banten Regency, obtained information that in 2022 out of 365 mothers who gave birth, 157 cases were found with prolonged labor so that sometimes referrals were made, while the rebozo technique and oxytocin massage had not been carried out at that location. Purpose of Writing: Knowing the comparison of giving the rebozo technique and oxytocin massage to the length of the second stage in mothers giving birth at the Dian Medika Jayanti Clinic, Tangerang Regency. Research Method: quasy experiment with posttest only design with control group design. The sample is 30 mothers giving birth with total sampling technique. Intervention for 5-10 minutes and repeated 3 times. Bivariate analysis using the Mann Whiteney test. Results: The results of the univariate study mean the length of the second stage of labor by administering the rebozo technique was 58.00 minutes and 30.93 minutes. The average length of the second stage of labor with oxytocin massage was 67.00 minutes. The results of the Mann Whiteney bivariate test for the second stage of labor were 0.021. Conclusions and Suggestions: There are differences in giving the rebozo technique and oxytocin massage to the length of the second stage of labor in mothers. Midwives are expected to speed up the delivery process, it would be better if the rebozo technique and oxytocin massage were given simultaneously so that the progress of labor would go faster.